Metodologia de seleccion por eficiencia en el uso del fosforo y por tolerancia a la toxicidad del aluminio y del manganeso en el frijol (Phaseolus vulgaris L.) - Thung, M.; Ortega, J.; Erazo, O (International Center for Tropical Agriculture, 1990)
Soil P, Al, and Mn, and P deficiency and Al and Mn toxicities in the bean plant are reviewed. Results of trials conducted at CIAT- Quilichao to determine P, Al, and Mn stress levels in bean lines are given. The methodology for bean germplasm screening for efficient P use and tolerance to Al and Mn toxicity is described. Most lines which were identificated till now as tolerant come from Brazil. (CIAT)